2014
DOI: 10.3390/ijerph110403870
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Organically Grown Crops to Human Health

Abstract: An increasing interest in organic agriculture for food production is seen throughout the world and one key reason for this interest is the assumption that organic food consumption is beneficial to public health. The present paper focuses on the background of organic agriculture, important public health related compounds from crop food and variations in the amount of health related compounds in crops. In addition, influence of organic farming on health related compounds, on pesticide residues and heavy metals i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 151 publications
(226 reference statements)
6
86
0
Order By: Relevance
“…However, season is well known to be a major contributor to variation in most types of compounds in the majority of all crops (Donno et al, 2013;Francisco, Cartea, Soengas, & Velasco, 2011;Johansson et al, 2014;Liu et al, 2014;Malik, Prieto-Linde, Kuktaite, Andersson, & Johansson, 2011;Tabart et al, 2006;Zheng et al, 2012). One factor that may have influenced the results of the present study is that the bushes were not pruned during season 1, but later when the bushes were actively used in this research project, pruning activities were carried out for the remaining seasons.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, season is well known to be a major contributor to variation in most types of compounds in the majority of all crops (Donno et al, 2013;Francisco, Cartea, Soengas, & Velasco, 2011;Johansson et al, 2014;Liu et al, 2014;Malik, Prieto-Linde, Kuktaite, Andersson, & Johansson, 2011;Tabart et al, 2006;Zheng et al, 2012). One factor that may have influenced the results of the present study is that the bushes were not pruned during season 1, but later when the bushes were actively used in this research project, pruning activities were carried out for the remaining seasons.…”
Section: Discussionmentioning
confidence: 67%
“…A recent review has also shown that among bioactive compounds, phenolic compounds are a major contributor to human health (Johansson, Hussain, Kuktaite, Andersson, & Olsson, 2014). A growing body of scientific data is being accumulated confirming that different parts of the black currant plant (buds, leaves and fruits) are important sources of beneficial phenolic compounds (Donno, Beccaro, Mellano, Cerutti, & Bounous, 2013;Raudsepp, Kaldm€ ae, Kikas, Libek, & PĂŒssa, 2010;Tabart, Kevers, Evers, & Dommes, 2011;Tabart et al, 2007).…”
Section: Introductionmentioning
confidence: 95%
“…With the exception of the two most recent studies from the prospective pregnancy cohort in Norway (19,106), the remaining studies have been included in one or more of a number of scientific reviews and reports (7,17,27,29,46,50,55,73,82,99). The human studies include only five prospective cohort studies, and there is a general consensus that the scientific evidence from human studies is insufficient to conclude whether organic food is more beneficial for health in some respects than are conventional food.…”
Section: Summary Of Health Effects Studiesmentioning
confidence: 99%
“…This prevention is the only option for low-income populations who will not be able to afford the additional costs of treatment for cardiovascular diseases, stroke, cancers, and metabolic diseases (Johansson et al, 2014). Some vegetables do even exert curative effects, such as lowering blood sugar and serum cholesterol levels, influencing the development of malignant tumours (cancerogenesis), and other disease-related conditions.…”
Section: Tanninsmentioning
confidence: 98%